Quantification of metallic artifact on CT associated with titanium pedicle screws - Lewis, M. J.; Early, P. J.; Bergman, R.; Love, K.; Nelson, N. (Frontiers in Veterinary Science, 2024)
Background: In dogs undergoing vertebral column stabilization, post-operative computed tomography (CT) evaluates implant placement. The impact on interpretation of metallic artifact associated with titanium implants in dogs remains to be established. Our objective was to quantify metallic artifact on CT associated with titanium pedicle screws. Methods: Study design included an in vitro model and retrospective review of 11 dogs with vertebral column stabilization. Twenty-four titanium pedicle screws (6 each: 2.0mm, 2.7mm, 3.5mm, 4.5mm) were placed into a 20% ballistic gel, and CT of the construct was performed. Three blinded raters measured maximum width (effective size) for each screw using a bone window; one rater measured effective size using an ultrawide window and 45 titanium pedicle screws (3x2.0mm, 5x2.7mm, 30x3.5mm, 7x4.5mm) in 11 clinical cases. Effective size measurements were compared to actual screw sizes. Results: Effective size was 26.9-43.8%, 9.2-18.5%, and 21.1-30.5% larger than actual size for the in vitro system (bone window), the in vitro system (ultrawide window), and clinical cases, respectively. Mean gross difference for the in vitro measurements varied by implant size (p < 0.001) and positively correlated with implant size (r = 0.846), but mean percentage difference negatively correlated with implant size (p < 0.001). Overestimation was larger for the in vitro model bone window compared to the ultrawide window (p < 0.001) and clinical cases (p = 0.001). Conclusions: Metallic artifact associated with titanium pedicle screws on CT resulted in overestimation of screw size. This information might aid in interpretation of implant placement on post-operative imaging.